Advances and Surgical Considerations in the Treatment of Moyamoya Disease. (1st February 2014) - Arias, Eric J.; Derdeyn, Colin P.; Dacey, Ralph G.; Zipfel, Gregory J.
Abstract: Moyamoya is a rare disorder that involves steno-occlusive arterial changes of the anterior circulation, along with proliferative development of basal arterial collaterals. It is either idiopathic (called moyamoya disease) or the result of a specific underlying condition such as atherosclerosis, radiation therapy, or sickle cell disease (called moyamoya syndrome or phenomenon). In recent years, numerous insights into and advances in the understanding, evaluation, and management of moyamoya patients have occurred. This article briefly reviews the spectrum of moyamoya conditions and then provides a synopsis of numerous recent investigations that shed light on various aspects of the disease, including its clinical characteristics, natural history, underlying pathology, imaging, surgical techniques, and long-term patient outcome.